The role of psychological empowerment in climate-protective consumer behaviour: An extension of the value-belief-norm framework. (29th January 2018) - Hartmann, Patrick; Apaolaza, Vanessa; D'Souza, Clare
Abstract : Purpose: This paper aims to address the role of psychological empowerment in proenvironmental consumer behaviour, focussing on climate protection. Design/methodology/approach: Study 1 analyses the interaction of the effects of psychological empowerment and personal norms on two environmental behaviours with a sample of 600 individuals drawn form a representative online panel of the Australian population. Study 2 addresses the reinforcing influence of empowerment with a quasi-experimental design comparing 300 consumers of green electricity with 300 conventional electricity clients. Findings: Psychological empowerment moderates the effects of personal norms on climate-protective consumer behaviour in a value-belief-norm (VBN) framework. Personal norms have a stronger influence for consumers experiencing high psychological empowerment than for disempowered feeling consumers. Furthermore, psychological empowerment experienced as an outcome of actual proenvironmental behaviour mediates the relationship between prior climate protection and future climate-protective intentions. Research limitations/implications: Future research should focus on the experimental manipulation of psychological empowerment with communicational claims, studying how perceived empowerment can be enhanced. Practical implications: To promote climate friendly products and behaviours, marketers should use communication claims aimed at enhancing consumer's subjective experience of empowerment. Social implications: Public policy aimed at climate protection should focus on consumer education increasing consumers' awareness of their potential influence. Originality/value: Psychological empowerment has not been studied previously as either an antecedent or outcome of proenvironmental behaviour. This is the first study to show that psychological empowerment moderates normative influences on climate-protective consumer behaviour. This research further reveals a novel behavioural reinforcement process, in which psychological empowerment intervenes as a behavioural outcome as well as an antecedent of climate-protective consumer behaviour. Findings contribute to the development of the VBN framework as well as to the consumer-empowerment perspective on proenvironmental behaviour.